Bacteroides thetaiotaomicron enhances H2S production in Bilophila wadsworthia - Jade Davies; Melinda J. Mayer; Nathalie Juge; Arjan Narbad; Lizbeth Sayavedra (Gut Microbes)
Sulfate- and sulfite-reducing bacteria (SRB) are a group of strict anaerobes found within the human gut. Bilophila wadsworthia, a sulfite-reducing bacterium which produces hydrogen sulfide (H2S) from taurine and isethionate respiration, is a common member of the healthy commensal human gut microbiota but has been implicated in several disease states including inflammatory bowel disease and colorectal cancer. Bacteroides thetaiotaomicron, one of the most prominent gut bacteria, has sulfatases which release sulfate, serving as a potential substrate for sulfate-reducing bacteria. Here, we showed that when B. thetaiotaomicron and B. wadsworthia were in co-culture, there was a significant increase in B. thetaiotaomicron’s growth and in H2S production by B. wadsworthia. Differential gene expression analysis revealed increased expression of B. wadsworthia’s dsrMKJOP complex in co-culture, which delivers electrons for sulfite reduction to H2S. This was accompanied by a decreased expression of genes associated with taurine, sulfolactate, and thiosulfate respiration, indicating that B. thetaiotaomicron may provide an alternative source of sulfite to B. wadsworthia. We hypothesized adenosine 5’-phosphosulfate (APS) to be this intermediate. Indeed, B. wadsworthia was able to grow using APS or sulfite as electron acceptors. Endometabolomic and transcriptomic analyses revealed decreased production of indole by B. thetaiotaomicron in co-culture with B. wadsworthia due to enhanced tryptophan utilization by B. wadsworthia. The results of this microbe−microbe interaction could have significant pro-inflammatory effects in the human gut environment.